Occurrence and characterization of Shiga toxin-producing Escherichia coli from goats on communal rangeland in Gauteng South Africa - Karama, Musafiri (University of Pretoria, 2025)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2022.